The Relationship between Religion and Cultural Rituals (A Comparative Study of the Tedhak Siten and Toron Tana Traditions) - Ihwan Amalih; Miftahul Jannah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The relationship between religion and culture is a constantly evolving discourse in Islamic and socio-cultural studies. Religion is often understood as sacred and transcendental teachings, while culture is viewed as a social product born of human creativity. However, in the reality of Indonesian society, the two often exist in a dialogue and are intertwined. This study aims to examine the relationship between religion and cultural rites in the Tedhak Siten tradition in Javanese society and the Toron Tana tradition in Madurese society, as well as to analyze the similarities and differences in the patterns of the relationship between religion and cultural rites in both traditions. This study uses a qualitative approach with a comparative research method. Data were obtained through observation, interviews, and documentation in two research locations: Tuban Village, Gondangrejo District, Madura Regency. Karanganyar and Lemper Village, Pademawu District, Pamekasan Regency. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the Tedhak Siten and Toron Tana traditions represent a form of acculturation between Islamic teachings and local culture, passed down through generations. Islamic religious values ​​are reflected in the recitation of prayers, gratitude to Allah SWT, and hopes for the safety and future of the child. The similarities between the two traditions lie in their symbolic function as rites of passage for infants in the early stages of life and as a medium for internalizing religious and social values. Differences are evident in the stages of the procession, ritual equipment, and the emphasis on cultural symbols, which are influenced by the social context and cultural environment of each community. This study concludes that religion and culture in the Tedhak Siten and Toron Tana traditions are not dichotomous but rather mutually reinforcing in shaping the religious character of the local community